Globalization, poverty, inequality, and insecurity: Some insights from the economics of happiness - Carol Graham (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
The literature on the economics of happiness in the developed economies finds discrepancies between reported measures of wellbeing and income measures. The `Easterlin paradox', for example, shows that average happiness levels do not increase as countries grow wealthier. This article explores how the economics of happiness can help explain gaps between standard measures of poverty and inequality and reported assessments of welfare in countries in the process of integrating into the global economy. Most prominent among these discrepancies is that between economists' assessments of the benefits of globalization for the poor and those made by the general public. Survey research often highlights phenomena that are not typically captured by money metric measures, such as vulnerability to poverty among the near poor and distributional shifts at the local, cohort, and sector level. The article posits that the gaps between income measures and reported wellbeing may matter to development outcomes, based on evidence from the author's research on reported wellbeing in Latin America and Russia. – welfare ; wellbeing ; happiness
Keywords: I31; I32; 330; Lebensqualität; Armut; Messung; Globalisierung; Entwicklungsländer; Lateinamerika; Russland